2021
DOI: 10.1007/s12325-021-01711-z
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in Clinical Cardiology 2020: A Summary of Key Clinical Trials

Abstract: Introduction Despite the challenge of a global pandemic, 2020 has been an invaluable year in cardiology research with numerous important clinical trials published or presented virtually at major international meetings. This article aims to summarise these trials and place them in clinical context. Methods The authors reviewed clinical trials presented at major cardiology conferences during 2020 including the American College of Cardiology, European Association for Percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the single-arm design precludes a direct comparison to other DES. Nevertheless, these first 36-month outcomes of this innovative device are relevant and the trial was listed in the Advances in Clinical Cardiology Summary of Key Clinical Trials [ 25 ]. Several trials are currently ongoing to assess the device in larger patient populations with more complex lesions, and to compare it against contemporary DES in randomized settings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the single-arm design precludes a direct comparison to other DES. Nevertheless, these first 36-month outcomes of this innovative device are relevant and the trial was listed in the Advances in Clinical Cardiology Summary of Key Clinical Trials [ 25 ]. Several trials are currently ongoing to assess the device in larger patient populations with more complex lesions, and to compare it against contemporary DES in randomized settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vascular inflammation is considered to have a central role in the pathophysiology of atherosclerosis and colchicine , due to its anti-inflammatory properties, has been shown to be beneficial in secondary prevention (AKODAD et al, 2020;KEARNEY et al, 2021).…”
Section: Colchicine In the Vascular Inflammatory Processmentioning
confidence: 99%
“…Currently, the diabetic population is becoming younger, and the International Diabetes Federation has reported that the total number of people with diabetes is expected to reach 642 million by 2040 [ 1 , 2 ]. Hyperglycemia, the underlying cause, not only aggravates the debilitating illness, but is one of the significant risk factors for increasing cardiovascular, renal or retinal complications [ 3 , 4 , 5 ]. Diabetic patients are likely to develop cardiovascular complications, which contributes to the high morbidity and mortality associated with the disease.…”
Section: Introductionmentioning
confidence: 99%